HOPELESSNESS DITINJAU DARI KEPUASAN HIDUP PADA PASIEN KANKER PAYUDARA DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Henni Sinthya (Universitas Negeri Makassar, 2019)
This study aims to examine the relationship between life satisfaction with hopelessness. The hypothesis of this research is that there is neagtive relationship between life satisfaction and hopelessness among breast cancer patients. This research used correlational quantitative methods. Participants in this research was 100 breast cancer patients, which was taken by purposive sampling technique. Data were collected using the Hopelessness Scale from Farran, Herth & Popovich (in Canisti, 2012) and life satisfaction measured by Life Satisfaction Scale. The correlation was analyzed using the Pearson Correlation Test with SPSS 18 for Windows. The results showed there was a negative and significant relationship between life satisfaction and hopelessness (r=-0,260; p=0,000) which means the higher life satisfaction, the hopelessness.